ARE ORGANIZATIONAL COMMITMENT AND EMPLOYEE ENGAGEMENT IMPORTANT IN ACHIEVING INDIVIDUAL READINESS FOR CHANGE? - Wustari L.H. Mangundjaya (HUMANITAS: Indonesian Psychological Journal, 2012)
AbstractGlobalization is everywhere, in this regard, every organization should change according to the needs and requirement of the environment. In addition, in today’s economy, it’s critical to have effective, and efficient organization. Failure to effectively engage employees can result in wasted resources, unboptimal organizational performance, and deteriorating employee morale. On the other hand, successfully engaging and committing employee can result in higher levels or organizational performance as well as higher levels of job satisfaction, both of which are much needed in today’s environment.The question arises whether organizational commitment, and employee engagement are related to individual readiness for change. The objective of this research is to identify the relationship andimpact between organizational commitments, employee engagement to individual readiness to change. This study done in four financial companies, that consist of three private owned banks and one government owned financial company (N= 502), with quantitative methods and correlation survey. The results showed that both organizational commitment and employee engagement are positively relatd and have contributed toindividual readiness to change. The results also show that the correlation of organizational commitment is stronger than employee engagement to individual readiness to change.Keywords: organizational commitment, employee engagement, individual readiness to change.